Analysis of the Increase in Performance and Welfare Allowances for Researchers at the Indonesian Research and Development Institute - Puspita, Listia Sari (Journal Research of Social Science, Economics, and Management, 2026)
This research analyzes the performance allowance policy and welfare of ASN researchers at LIPI who have currently joined the National Research and Innovation Agency (BRIN) with a focus on their potential impact on productivity. Different from previous studies that highlighted well-being, this study evaluated the relationship between incentives and the number of publications on Google Scholar and Scopus using qualitative descriptive analysis. Data from 2012, 2015, 2019, and 2022 show an imbalance between incentives and productivity, where senior researchers receive larger increases in benefits even though their productivity does not increase proportionately. The results show that incentive policies are based more on the hierarchy of positions than the potential productivity of researchers. These results indicate that the current incentive policy is more strongly determined by job hierarchy than by actual scientific productivity. In conclusion, although the increase in performance allowances contributes to improving researchers’ welfare, the policy has not yet fully functioned as an effective instrument for stimulating publication productivity. Therefore, a more balanced and performance-oriented incentive scheme is needed to better align welfare improvement with the goal of strengthening national research competitiveness